Severe Mitral Regurgitation in a Child With Henoch-Schönlein Purpura and Pulmonary Hemorrhage - Cornelius A. James MD; Ismael Gonzalez MD; Paras Khandhar MD; Bishara J. Freij MD (SAGE Publishing, 2017)
Introduction: Henoch-Schönlein purpura (HSP) is the most common vasculitis of childhood. The classic triad of HSP consists of nonthrombocytopenic purpura, arthritis/arthralgia, and gastrointestinal complaints. Pulmonary hemorrhage and cardiac involvement are rare complications of HSP. Case Report : We report the case of a 10-year-old girl with HSP complicated by both severe mitral regurgitation and pulmonary hemorrhage. Discussion : HSP is typically a self-limited illness with an excellent prognosis in children. Pulmonary hemorrhage is a rare complication that increases morbidity and mortality; it generally indicates the presence of severe vasculitis. Cardiac involvement in HSP is extremely rare and associated with a poor prognosis. Conclusion : Cardiac involvement in HSP may be more common than believed. Because of the increased morbidity and mortality associated with HSP complicated by pulmonary hemorrhage and cardiac involvement, it is important for clinicians to be aware of these potential complications.